تحسين تطبيق مبدأ الإدارة البينية المتكاملة في المشاريع الهندسية باستخدام صيغة تصدير النماذج IFC ضمن منظومة BIM - خير بك, علي; ميّا, رنا; سخطة, بنان رياض (Latakia University Journal -Engineering Sciences Series, 2016)
فرض تعدّد مراحل دورة حياة المشروع وتنوع الأطراف المشاركة فيه وكثرة البرمجيات المستخدمة والتي تختلف حسب تعددّ الاختصاصات في المشروع تعقيداً كبيراً في صناعة التشييد بحيث جعل من تحقيق التكامل والانسجام فيما بينها مطلباً أساسياً. تم في هذا البحث تصميم استبيان لتقييم وجود منهجيات لإدارة البيانات في مؤسسات القطاع العام المعنية بإنجاز دراسات هندسية، أظهر المسح غياب وجود أنظمة اتصال لإدارة البيانات بنسبة 80% ومدد استغرقتها عملية نقل وتبادل البيانات وصلت لشهرين ونصف، مع ورود ملاحظات عن عدم وضوح لبعض تفاصيل الدراسة بنسب تراوحت بين 19% الى 80%، مما يعطي فكرة عن عدم جدوى الطريقة التقليدية للمراسلات التي تستهلك الوقت والجهد. لذلك تم اقتراح تطبيق إدارة فاعلة لمعلومات ومعايير التصميم تدعم التنسيق بين الأطراف كافة "Interoperability" بتفعيل أداة برمجية وهي Tekla bim sight. أظهر تطبيق البرمجية على دراسة حالة فاعلية جيدة لتحسين تطبيق الإدارة البينية المتكاملةInteroperability لتسمح باستعراض جميع البيانات المتعلقة بالمشروع وبتفاصيلها كافة ومن قبل الاطراف كافة وبالتالي سهولة إدارتها. According to the numerous stages of the projects, the variety parts involved and the much more software used which differ according to the fields in the project. All of that led to a great complexity in the construction industry that made integration and collaboration as a basic requirement. A questionnaire is being designed to estimate methodologies relating to data transfer and exchange in the public sector. This survey showed an absence of any recent communication systems to manage and exchange data at 80% and the estimated duration to transfer data took beyond 2 months with feedback remarks about mysterious details in the design reached 80% , That showed a worthless way of transferring and exchanging data which consumes time and effort .That's why suggesting the application of an effective data management will support the coordination and communication between all parts by activating a software tool called Tekla bim sight . The application of the previous tool on a case study showed an efficiency to improve interoperability application that helped to view all detailed data related to the project by all parts, that is why we can guarantee seamless data flow between all parts.